CHARACTERISTICS OF JELLY CANDY OF PAPAYA (Carica papaya L.) WITH ADDITION OF COW GELATIN - Neswati Neswati (BPFP Faperta UNIB, 2013)
Papaya is very potential to be developed as an industrial raw material candy because it contains a number of phytochemical compounds that are beneficial for the body. This study aims to investigate the characteristics of jelly candy of papaya with addition of cow gelatin by 6%, 8% , 11% and 13%. In jelly candy made observations on pH, moisture content, ash content, reducing sugar content, sucrose content, vitamin C content, total acid, antioxidant activity by DPPH, total plate count, organoleptic and the best jelly candy analysis of beta-carotene The results showed that the addition of 11% cow gelatin to produce the best characteristics of jelly candy. The parameters are pH 4.83, 17.63% moisture content, ash content of 0.98% , 19.75% reduction sugar , sucrose content of 35.48%, levels of vitamin C 59.81 mg/100gr material, total acid 2.09%, 35.33% antioxidant activity, total plate count 3.9 x 103 colonies/g, 7.9934 mg/100 g levels of beta-carotene, and organoleptic tests with a level, 95% color, scent 85%, 85% flavor, and texture of 95%.